2015
DOI: 10.11591/ijphs.v4i3.4736
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental Monitoring on Adolescence Premarital Sexual Behavior in Pontianak City, Indonesia

Abstract: Inadaquate parental monitoring is widely recognized as a risk factor for the development of child and adolescent conduct problems, including early premarital sexual behavior. Previous studies examining parental monitoring have largely effect to adolescents premarital sexual behavior. Parental monitoring is the most important and effective factor to prevent early adolescents sexual activity. This paper examines the role of perceived parental monitoring in adolescent’s premarital sexual behavior (study on Adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
2
10
0
6
Order By: Relevance
“…The affective factor influenced the maintenance of RH behavior. These findings confirm that interpersonal and situational contexts are related to RH behavior and correspond with the findings of previous research in which family norms [28] and social and cultural contexts [3] were related to RH behavior among Indonesian adolescents. Parents and peers were interpersonal influences on adolescent development.…”
Section: Discussionsupporting
confidence: 91%
“…The affective factor influenced the maintenance of RH behavior. These findings confirm that interpersonal and situational contexts are related to RH behavior and correspond with the findings of previous research in which family norms [28] and social and cultural contexts [3] were related to RH behavior among Indonesian adolescents. Parents and peers were interpersonal influences on adolescent development.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, other findings (Markham et al, 2003;Henrich et al, 2006;Suwarni et al, 2015;Romer et al, 1999) found family environment as an important factor affecting perception of premarital sex. This study did not look at the role play by family environment in shaping perception of premarital sex.…”
Section: Discussionmentioning
confidence: 97%
“…Markham et al findings indicate that students who perceived high levels of family connectedness were less likely to engage in premarital sexual activity. Other studies by Suwarni et al (2015) Donenberg et al,(2002, Bryant (2002) and Mehrotra et al (2013) suggest that parental monitoring is assoicated with premarital sex among youths. They stated that with less parental monitoring, youths are more likely to engage in premarital sex.…”
Section: Factors That Impact On Premarital Sexual Activitymentioning
confidence: 91%
“…Davis (1989) menyatakan persepsi manfaat sebagai sajauh mana seorang percaya bahwa menggunakan suatu teknologi akan meningkatkan kinerjanya. Penelitian sebelumnya yang dilakukan oleh Davis (1989), Wibowo et al (2015), Ahmad & Pambudi (2014), Suwarni et al (2015), Romadloniyah & Prayitno (2018) menunjukan bahwa konstruk persepsi manfaat memengaruhi secara positif dan signifikan terhadap penggunaan sistem informasi. Jika seseorang merasa percaya bahwa suatu teknologi berguna maka dia akan menggunakannya, sedangkan jika menurutnya teknologi tersebut kurang berguna maka dia tidak akan menggunakannya.…”
Section: Pendahuluanunclassified